(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2026)
This article analyzes the conceptual model, functional structure, and institutional significance of the information system of the unified digital platform of the National Qualifications System, developed on the initiative of the Institute for the Development of the National Qualifications System. The study aims to strengthen the link between the labor market and the education system through digitalization, regulate qualification requirements, and improve the efficiency of assessment processes. The article covers the development and registration of occupational standards and sectoral qualification frameworks, accreditation and monitoring of assessment centers, as well as digital exams, appeals, and QR-coded certificates. It also examines opportunities for creating online resumes, organizing distance learning and testing, and accessing regulatory documents in real time. The results show that the system reduces paperwork, saves time, and increases management efficiency. In conclusion, the platform plays an important role in strengthening the National Qualifications System and supporting human capital development.